2007
DOI: 10.1007/s00253-007-1176-5
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous nitrification and denitrification by diverse Diaphorobacter sp.

Abstract: Eight bacterial isolates closely related to Diaphorobacter sp. were isolated from activated biomass surviving on wastewater laden with dyes and nitro-substituted chemicals and were identified by 16S rDNA sequence analysis. The isolates showed sequence similarity of 99-100% to other Diaphorobacter strains such as ZY 2006b, F2, NA5, PCA039, D. nitroreducens KSP4, and KSP3 and 98-99% sequence homology to D. nitroreducens NA10B (type strain JCM 11421). Neighbor-joining tree revealed that all the eight strains form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 202 publications
(88 citation statements)
references
References 29 publications
2
81
1
2
Order By: Relevance
“…Characteristics of No.4 have been previously described in details [11]. Cultured cells of No.4 were mixed with a 50% glycerol solution in vials and stored at -84°C.…”
Section: Strain Usedmentioning
confidence: 99%
See 1 more Smart Citation
“…Characteristics of No.4 have been previously described in details [11]. Cultured cells of No.4 were mixed with a 50% glycerol solution in vials and stored at -84°C.…”
Section: Strain Usedmentioning
confidence: 99%
“…When high-strength ammonium is involved in CW, COD in the wastewater is not sufficient to complete the removal of ammonium [1][2][3][4][5]. Recently, many bacteria have been known to be capable of heterotrophic nitrification and aerobic denitrification [6][7][8][9][10][11][12][13][14]. The use of these bacteria provides advantages over the conventional nitrogen removal process of aerobic nitrification and an anaerobic denitrification because ammonium removal is achieved in one reactor using one type of bacteria under aerobic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Khardenavis et al [29] reported that Diaphorobacter strains isolated from activated sludge were capable of simultaneous nitrification and denitrification under aerobic conditions. In this respect, it is interesting to investigate whether D. nitroreducens is capable of heterotrophic nitrification.…”
Section: Discussionmentioning
confidence: 99%
“…3b). Richardson et al (1998) indicated that the heterotrophic nitrification process and aerobic denitrification process are (Chen et al, 2012;Khardenavis et al, 2007;Robertson et al, 1988). In comparison, for strain SYF26, conversion of nitrate was observed during the process of ammonium removal, and both nitrite and nitrate could be denitrified efficiently under aerobic conditions.…”
Section: Utilization Of Nitrite and Nitrate By Strain Syf26 Under Aermentioning
confidence: 99%
“…Heterotrophic nitrifying-aerobic denitrifying micro-organisms capable of nitrification and denitrification simultaneously under aerobic conditions have drawn increasing attention (Chen & Ni, 2011;Khardenavis et al, 2007;Zhu et al, 2012). To date, certain groups of heterotrophic nitrification-aerobic denitrification micro-organisms, such as Paracoccus denitrificans (formerly known as Thiosphaera pantotropha), Alcaligenes faecalis, Pseudomonas stutzeri, Microvirgula aerodenitrificans and Bacillus have been isolated from soils and wastewater treatment systems (Kim et al, 2008;Yang et al, 2011;Joo et al, 2006).…”
Section: Introductionmentioning
confidence: 99%